Staging anxiety through magical realism: A practice-based exploration in two theatrical productions - Punpeng, Grisana (Humanities, Arts and Social Sciences Studies, 2024)
Anxiety disorders are prevalent in everyday life, yet theatrical realism often struggles to capture and convey the lived experiences from the points of view of those affected. This practice-based research explores how magical realism can serve as an alternative mode of representation to depict the internal experiences of characters with anxiety disorders on stage. The study began with a literature review on magical realism and anxiety disorders, identifying key characteristics that informed the development of performances. Through a devising process, the research culminated in two distinct productions: “The Practice,” a devised piece created with a group of seven actors and showcased at the Bangkok Theatre Festival in November 2022, and “As Fa As Farida,” a solo performance developed collaboratively by the researcher-director and an actor, staged in May and June 2023 at the Faculty of Communication Arts, Chulalongkorn University. Despite differences in scale and presentation, both performances were able to portray the inner worlds of characters with anxiety disorders through the essence of magical realism, characterized by four main themes identified through thematic analysis: the interplay of reality and fantasy, the disruption of space and time, metatheatrical reflections on society and identity, and voices from the margins. The insights from this study can guide future theatrical experiments and be applied across various media, including literature, film, and other art forms.